2021
DOI: 10.3389/fmed.2021.656792
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of High-Dose Dexamethasone vs. Other Treatments for Newly Diagnosed Immune Thrombocytopenia: A Meta-Analysis

Abstract: Objective: To compare the therapeutic efficacies of high dose dexamethasone, prednisone and rituximab in combination with dexamethasone for newly diagnosed ITP (Immune Thrombocytopenia, ITP) patients.Methods and results: Relevant publications for this study were obtained by searching PubMed, Embase, Cochrane, and CNKI (National Knowledge Infrastructure, CNKI) databases following the PRISMA guidelines. A total of, 15 publications were retrieved that contained sufficient data from 1,362 patients for high quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 26 publications
1
11
1
Order By: Relevance
“…Response time to treatment could be an attractive prognostic indicator in ITP, but evidence was lacking. In one study, high dose dexamethasone produced faster platelet response than prednisone (3 to 5 days respectively) but in twelve months follow-up, complete response rates were comparable (32.1 % for high dose dexamethasone and 34.1 % for prednisone) [13]. We also found that faster response time did not produce longer remissions, but faster response time produced significantly higher remission rates, and this was compatible with the literature.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Response time to treatment could be an attractive prognostic indicator in ITP, but evidence was lacking. In one study, high dose dexamethasone produced faster platelet response than prednisone (3 to 5 days respectively) but in twelve months follow-up, complete response rates were comparable (32.1 % for high dose dexamethasone and 34.1 % for prednisone) [13]. We also found that faster response time did not produce longer remissions, but faster response time produced significantly higher remission rates, and this was compatible with the literature.…”
Section: Discussionsupporting
confidence: 90%
“…Corticosteroids are the main backbone of first line treatment; prednisolone, methylprednisolone and high dose dexamethasone was used effectively for treatment. High dose dexamethasone seemed to induce faster response and less long-term toxicity compared to prednisone [13], but overall prognosis of the disease did not significantly change in either of treatment and, at 12 months response rates were similar [14]. According to ASH guidelines for immune thrombocytopenia, both can be used as a primary treatment [12].…”
Section: Discussionmentioning
confidence: 99%
“… 22 , 29 However, a study by Xiao et al. 30 reported no difference in adverse event or relapse rate between the two regimens, while dexamethasone tend to reach a higher sustained response. Our results are favorable to dexamethasone both in short-term and long-term response, as well as the incidence of grade ≥3 AEs, though they had no obvious statistical difference using pairwise meta-analysis.…”
Section: Discussionmentioning
confidence: 98%
“…With additional data on high‐dose dexamethasone treatment available, there was a new metanalysis done by a Chinese group 23 . In arm A they compared HD‐DXM to PDN and in arm B dexamethasone to the combination of rituximab and dexamethasone.…”
Section: Dexamethasone Treatment In Newly Diagnosed Itpmentioning
confidence: 99%
“…With additional data on high-dose dexamethasone treatment available, there was a new metanalysis done by a Chinese group. 23 In arm A they compared HD-DXM to PDN and in arm B dexamethasone to the combination of rituximab and dexamethasone. They found HD-DXM to be superior to PDN in OR at one month [response rate (RR) = 1.12; 95% confidence interval (CI) = 1.03-1.22, p = 0.006] and in sustained response at 12 months (RR = 1.34; 95% CI = 1.06-1.68, p = 0.014).…”
Section: De X a M Eth Ason E Tr E Atm E N T I N N Ew Ly Di Agnose D Itpmentioning
confidence: 99%